Comparing Anxiety Levels: Male vs. Female College Students - Dr Aruna (Innovative Research Thoughts, 2017)
The purpose of this casual comparative study was to investigate whether there is a significant difference in anxiety levels between male and female college students of a rural area named Adampur in Haryana, India. The present study has been carried out on a sample of 60 college students (Male and Female) with their age ranging between 17-21 years. The major instrument used in the present study was an anxiety test named Sinha's Comprehensive Anxiety Scale (SCAT) was developed by AKP Sinha and LNK Sinha in the year 1995. The scale contains 90 items. The subject were selected on the basis of random sampling. After collection of the data, statistical analysis has been done with the help of statistical tools of descriptive statistics and T-test. The findings of the study are indicative that there is an insignificant difference between anxiety levels of the two genders.